Capitalism Is Destructive to Social Responsibility: Arthur Miller’s All My Sons - Atheer J. Muhsin (Genius Journals, 2021)
All My Sons, is the beginning of the great success of Arthur Miller right after World War II in 1947. The play is an ideal review of the writer's attitudes towards the capitalist system. At the same time, it is a presentation of individual and social relationships, personal and public responsibilities and individual and public interests. This research refers to the writer's criticism of the capitalist system by some of the characters in the play and its devastating effects on society, according to Arthur Miller’s viewpoint. The research also addresses the importance of personal responsibility towards society and the extent to which these responsibilities affect the behavior of the personalities. This research shows that the love of money and wealth is not an ultimate goal in life, and if it becomes so, it will become a destructive force, as what happened with Joe Keller's family. love of money and wealth
Keywords: Arthur Miller; Capitalist system; love of money and wealth